Letramento Estético na EJA e na Educação do Campo - Araújo, Gustavo Cunha de (Editora Oficina Universitária, 2020)
The work Aesthetic Literacy in EJA and Rural Education, originated from a doctoral study carried out in the Graduate Program in Education, at the Faculty of Philosophy and Sciences of UNESP, Marília campus, state of São Paulo, presents a didactic-training experiment developed with rural youth and adults. based on Historical-Cultural theory, this research reveals that the term literacy points to a set of social practices in the context of written culture in which subjects can engage. In the author's understanding, aesthetic literacy is a cultural asset to which children, young people and adults have an inalienable right, and the school and university have a duty to pay attention to the development of a didactic proposal aimed at bringing the reader closer to the text. Given this, it is considered that the perspective of science in general, art and culture as components of literacy with young people and adults can no longer be postponed. The author also highlights the importance of aesthetic literacy for raising awareness about the reality in which the subject is inserted and for understanding the role of creative activity in the constitution of human personality. Strictly speaking, this study has consequences for the organization of text production work in Rural Education, in particular, and in education in general. Therefore, we hope that this work can expand studies and debates about rural education, arts, new literacy studies and Youth and Adult Education, as well as the training of educators for rural areas. We wish everyone happy reading!